E-107 Intracranial venous hypertension induced by extracranial arteriovenous fistula mimicking dural arteriovenous fistula. (22nd July 2018) - Lim, J; Kwon, H; Koh, H; Choi, S; Kim, S
Abstract : Introduction: Intracranial venous hypertension can be caused by various causes, especially venous sinus thrombosis or dural arteriovenous fistula. Intracranial venous hypertension can manifest various clinical symptoms depending on vein drainage. We report a case of intracranial venous hypertension mimicked dural arteriovenous fistula due to extracranial arteriovenous fistula without any intracranial vascular lesions. Methods: A 35 – year – old female patient visited our clinic with right oculomotor nerve palsy. The patient had a history of insulin-dependent diabetes mellitus, end-stage renal disease, and hypertension 20 years ago and several extracranial arteriovenous fistulas were performed for hemodialysis. Magnetic resonance imaging (MRI) showed a strong suspicion of dural arteriovenous fistula, but digital subtraction cerebral angiogram did not show any dural arteriovenous fistula findings but internal jugular vein occlusion, severe stenosis of distal brachiocephalic vein was caused by a previous arterial fistula and venous reflex caused intracranial venous hypertension. Result: We performed the balloon angioplasty at severe stenosis of brachiocephalic vein. Post-balloon angioplasty angiogram showed no more intracranial venous reflux. Conclusion: Extracranial arteriovenous fisula can induce intracranial venous hypertension in the poor venous circulation case. Disclosures: J. Lim: None. H. Kwon: None. H. Koh: None. S. Choi: None. S. Kim: None.